Numerical (CFD) and experimental analysis of hybrid household refrigerator including thermoelectric and vapour compression cooling systems - ONAT, AYHAN; ALPMAN, EMRE; HARTOMACIOĞLU, SELİM (ELSEVIER SCI LTD, 2019)
Numerical and experimental analysis of a previously investigated hybrid household refrigerator (HHR), HHR I, were conducted in this study. To determine the optimum location for the thermoelectric cooler installed in HHR I, CFD analysis was performed. As a result of the CFD predictions, two new HHRs, namely HHR II and III, were created and experimentally investigated. CFD predictions showed a more uniform air velocity and temperature distributions inside the fresh food compartments of HHR II and III compared to HHR I. Additionally, experimental measurements indicated a considerable increase in the energy efficiency of HHR II and III. Their energy consumption was nearly identical and improvements of up to 10% and 27% at the ambient temperatures of 16 degrees C and 32 degrees C, respectively, were observed when compared to HHR I. Regarding the cooling time, no effect of the relocation of the TEC was observed at the TEC's nominal voltage of 24 V. (C) 2019 Elsevier Ltd and IIR. All rights reserved.
Keywords: Cooling; CFD analysis; Energy consumption; Refrigerator; Thermoelectric cooler; Vapour compression; DOMESTIC REFRIGERATOR; COMPUTATIONAL MODEL; THERMAL UNIFORMITY; DESIGN PARAMETERS; HEAT-TRANSFER; PELTIER; FLOW; OPTIMIZATION; COMPARTMENT; SIMULATION